2018
DOI: 10.3389/fncel.2018.00381
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin-Associated Protein 1A Regulates Store-Operated Calcium Entry in Medium Spiny Neurons From Transgenic YAC128 Mice, a Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is a hereditary neurodegenerative disease that is caused by polyglutamine expansion within the huntingtin (HTT) gene. One of the cellular activities that is dysregulated in HD is store-operated calcium entry (SOCE), a process by which Ca2+ release from the endoplasmic reticulum (ER) induces Ca2+ influx from the extracellular space. HTT-associated protein-1 (HAP1) is a binding partner of HTT. The aim of the present study was to examine the role of HAP1A protein in regulating SOCE in YA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Recent studies showed that the expression of huntingtin-associated protein 1A (HAP1) was elevated in the striatum in a mouse model of HD [113]. HAP1, similar to mHTT, activated SOCE by influencing IP 3 R1 [113,114]. In human neuroblastoma cells, the HD pathological phenotype was mediated by expression of the N-terminal fragment of mHTT, which increased SOCE in a STIM1-dependent manner [115].…”
Section: Relationship Between Stim Proteins Glutamate and Glutammentioning
confidence: 99%
“…Recent studies showed that the expression of huntingtin-associated protein 1A (HAP1) was elevated in the striatum in a mouse model of HD [113]. HAP1, similar to mHTT, activated SOCE by influencing IP 3 R1 [113,114]. In human neuroblastoma cells, the HD pathological phenotype was mediated by expression of the N-terminal fragment of mHTT, which increased SOCE in a STIM1-dependent manner [115].…”
Section: Relationship Between Stim Proteins Glutamate and Glutammentioning
confidence: 99%
“…SOCE has been implicated in various neuronal functions, such as neuronal plasticity [15,17], the expression and activity of PM receptors [18,19], neuronal excitability [6,20], and the regulation of gene expression [16]. Disruptions of SOCE have been implicated in several neurodegenerative diseases, including Alzheimer's disease [17,21], Huntington's disease [22,23], and epilepsy [6] (reviewed in [10,24]).…”
Section: Introductionmentioning
confidence: 99%
“…STIM2.1 is a negative regulator of SOCE, and STIM2.2 is the counterpart of STIM2 (Miederer et al, 2015). Both isoforms are equally expressed in MSNs (Czeredys et al, 2018), but their functions in the regulation of SOCE in neurons are unknown. STIM1 has high affinity for Ca 2+ and requires the higher depletion of Ca 2+ from the ER during SOCE.…”
Section: Neuronal Ca 2+ Signaling Via Store-operated Ca 2+ Channels Umentioning
confidence: 99%
“…It also blocks the inhibitory actions of ankyrin on IP3R3 (Wu and Bowen, 2008 ). In MSNs, where IP3R1 is a predominant neuronal isoform (Czeredys et al, 2018 ) S1R resisting in MAMs and stabilizes IP3R3 (Ryskamp D. A. et al, 2019 ). The S1R directly binds to IP3R1 and leads to the stimulation of protein kinase C (PKC) activity and suppression of IP3 synthesis in hepatocytes (Abou-Lovergne et al, 2011 ).…”
Section: Neuronal Ca 2+ Signaling Via Store-operatmentioning
confidence: 99%
See 1 more Smart Citation